Strong cation exchange chromatography: a new option for concurrent quantification of saxagliptin and metformin - Pankaj Manohar Kharabe, Deepali Kailas Kadam (Journal of Applied Pharmaceutical Science, 2021)
Extremely polar antidiabetic drug like metformin (MET) along with saxagliptin (SXP) often suffer from peak fronting/ tailing effects along with earlier elution with void volume in RP-HPLC. Therefore, alternative and complimentary to this RP-HPLC, the strong cation exchange (SCX) chromatography has been used for the simultaneous quantification of SXP and MET along with stability studies. This investigation was performed on the Phenomenex Luna SCX column (100 × 2.1 mm. id, 5 μm) where both SXP and MET were eluted with ammonium formate (15 mM):MeOH (83:17 v/v) for 10 minutes with isocratic elution at 1 ml/minutes flow rate and performed at 30°C, and monitored at 230 and 260 nm wavelength where the retention time of both SXP and MET were 2.290 and 3.520 minutes, respectively. The validation studies revealed good linearity over the concentration ranging between 35.5 and 500 μg/ml for SXP and 15.5–250 μg/ml for MET with r2 values were 1.00 and 0.999 respectively. The percentage (%) recoveries for SXP and MET were 100.37% (±1.24) and 100.39% (±1.22), respectively. Moreover, as resulted, the acid, peroxide and thermal induced stress conditions have not made any significant changes but 0.1N NaOH at 50°C induced the degradation of SXP and MET.
Keywords: RP-HPLC, SCX chromatography, MET, saxagliptin and metformin.